Immunostimulant effect of Chaetomorpha sp in Tilapia infected with Aeromonas hydrophila - Kurniawan, Ronal; Putri, Mega N.; Riswan, M.; Wahyuni, Sri; Mursawal, Asri (Syiah Kuala University, 2025)
Chaetomorpha sp is a type of green marcoalgae that is rich in bioactive compound that function as antibacterial, anti-inflammatory and can increase fish immunity. This study aims to determine the immunostimulating effect of Chaetomorpha sp macroalgae extract on the leukocyte profile of Tilapia infected with A. hydrophila. The experimental method used a completely randomized design (CRD) with four extract dose treatments (0, 25, 50, 75 mL/kg feed) and three replicates. The test fish used were 2.63 0.26g, reared in black tanks with a size of 60x30x30 cm, a volume of 80 L with a stocking density of 1 fish/4 L, and a recirculation system. Maintenance was carried out for 60 days with a frequency of feeding three times a day, namely 08.00 AM, 01.00 PM, and 05.00 PM, as much as 5% of body weight. The parameters observed were total leukocytes, leukocyte differentiation, and phagocytosis index. The results showed that the administration of Chaetomorpha sp extract significantly increased total leukocytes, lymphocyte differentiation, and phagocytosis index (p0.05). The dose of 50 mL/kg feed is the optimal dose that affects the leukocyte profile of Tilapia. T0 (without extract) experienced 100% mortality, while the treatment group showed increased resistance to infection. Bioactive compounds such as sulfated polysaccharides and flavonoids in Chaetomorpha sp are thought to play a role in stimulating the innate immune system. This study highlights the potential of Chaetomorpha sp as an alternative to antibiotics in sustainable tilapia aquaculture.